Yearly changes in dispersal and life‐history traits of Monochamus alternatus Hope with reference to its outbreak. (29th March 2020) - Sugimoto, Hiroyuki; Fukuta, Miki; Togashi, Katsumi
Abstract: The Japanese pine sawyer, Monochamus alternatus Hope, is the primary vector of the pinewood nematode, Bursaphelenchus xylophilus (Steiner et Buhrer) Nickle, the causative agent of pine wilt disease in East Asia. The range of B. xylophilus expands through the dispersal capability of its vectors and transport of host trees infested with the pathogenic nematode and its vector. Outbreaks of M. alternatus populations occur together with the epidemics of pine wilt disease, because the insect reproduces on host trees recently killed by the disease. We measured some dispersal and life‐history traits of adults for four years to determine the change in flight capability and life history of a field population of beetles in relation to an outbreak. The population monitored exhibited an outbreak and subsequent collapse. The greatest mean body mass, largest area of hind wings, smallest wing load, and shortest preoviposition period were observed in the year of outbreak. By contrast, there was no difference in the ovariole number between pre‐outbreak (latent) and outbreak years. The greatest mean hind wing area and smallest wing load suggest likely result in greater flight performance. As other studies showed, adult body mass is related positively to the flight performance and oviposition rate. Moreover, a shortened preoviposition period leads to a high reproduction rate. Thus, adults in outbreak populations are "superdispersers" because they are likely to have enhanced flight capability and reproduction power. This suggests that M. alternatus populations at the onset of a population outbreak enhance the expansion rate of B. xylophilus range more than those during the latent and pre‐outbreak periods.